PARP Inhibition Activates STAT3 in Both Tumor and Immune Cells Underlying Therapy Resistance and Immunosuppression In Ovarian Cancer - Martincuks, Antons; Song, Jieun; Kohut, Adrian; Zhang, Chunyan; Li, Yi-Jia; Zhao, Qianqian; Mak, Edward; Rodriguez-Rodriguez, Lorna; Yu, Hua; Cristea, Mihaela (Frontiers in Oncology, 2021)
Despite the promising activity of poly(ADP-ribose) polymerase (PARP) inhibitors (PARPi) in many cancer types with defects in the DNA damage response the majority of the treated patients acquire PARPi resistance and succumb to their diseases. Consequently, there is an urgent need to identify the mechanisms of PARPi resistance. Here, we show that PARPi treatment promotes STAT3 activation in ovarian cancer cells, tumor-associated immune cells and fibroblasts, resulting in PARPi resistance and immunosuppression. Comparison of ovarian cancer patient-matched tumor biopsies before and after PARPi therapy revealed that STAT3 activity was significantly higher in tumor cells and tumor-associated immune cells and fibroblasts post PARPi treatment. Moreover, one-time PARPi treatment activated STAT3 both in tumor cells as well as diverse immune subsets and fibroblasts. PARPi-treated immune cells exhibited decreased expression of immunostimulatory interferon (IFN)-γ and Granzyme B while increasing immunosuppressive cytokine IL-10. Finally, we demonstrate that the acquisition of PARPi resistance in ovarian cancer cells was accompanied by increased STAT3 activity. Ablating STAT3 inhibited PARPi-resistant ovarian tumor cell growth and/or restored PARPi sensitivity. Therefore, our study has identified a critical mechanism intrinsic to PARPi that promotes resistance to PARPi and induces immunosuppression during PARPi treatment by activating STAT3 in tumor cells and tumor-associated immune cells/fibroblasts.